2012
DOI: 10.1017/s0033291712002395
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of major depressive disorder and its predictors in the general population: results from The Netherlands Mental Health Survey and Incidence Study (NEMESIS)

Abstract: In this community sample, the long-term risk of recurrence was high, but lower than that found in clinical samples. Subjects who had had an MDE had a long-term vulnerability for recurrence. Factors predicting recurrence included illness- and stress-related factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
121
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(133 citation statements)
references
References 25 publications
5
121
6
1
Order By: Relevance
“…This finding is inconsistent with that of Hardeveld et al (2013), who, as part of the Netherlands Mental Health Survey and Incidence Study (NEMESIS), have found that a large number of previous episodes predicted a shorter time to recurrence. This discrepancy could be related to the naturalistic nature of this study.…”
Section: ; Hansen Et Al 2008)-most Notably Bycontrasting
confidence: 74%
“…This finding is inconsistent with that of Hardeveld et al (2013), who, as part of the Netherlands Mental Health Survey and Incidence Study (NEMESIS), have found that a large number of previous episodes predicted a shorter time to recurrence. This discrepancy could be related to the naturalistic nature of this study.…”
Section: ; Hansen Et Al 2008)-most Notably Bycontrasting
confidence: 74%
“…It perhaps suggests that having a history of mental health problems is indicative of lower overall resilience. We know from previous research that there are high relapse rates for depression and anxiety disorders [38][39][40]. It may therefore be important to target support programs and resilience-training to those with a history of mental health problems to help prevent future mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to morbidity, disability and costs, depression in unipolar major depressive disorder (UD) and as a major component of bipolar disorders (BDs) also increases mortality associated with other, cooccurring medical illnesses-notably including cardiovascular, endocrine and pulmonary diseases-in addition to its major contribution to risk of suicide and high levels of economic costs (Almeida et al, 2014;Fan et al, 2014;Miller et al, 2014;Ng et al, 2007;Osby et al, 2001;Tondo et al, 2007;Van der Kooy et al, 2007;Wulsin and Singal, 2003;Schaffer et al, 2015). Danger from mood disorders owes to their prevalence, high rates of recurrences, and risks of sustained affective morbidity and disability (Hardeveld et al, 2013;Sutin et al, 2013). Identified factors associated with morbidity and disability in both UD and BD include symptomatic severity in acute episodes, younger onset, more recurrences, psychiatric hospitalization, financial and legal problems, co-occurring anxiety, delay of treatment, and older current age (Melartin et al, 2004;Melchior et al, 2010;Montagnier et al, 2006;Seemüller, 2014).…”
Section: Introductionmentioning
confidence: 99%